Complications associated with cervical cerclage: A systematic review - Sanah Alani; Jessica Wang; Eva Suarthana; Togas Tulandi (Wolters Kluwer Medknow Publications, 2023)
Cervical cerclages are associated with improved live birth rates and have low short- and long-term risks. However, there have been reports of fistula formation or erosion of cerclage into the surrounding tissue. Those complications are uncommon and yet are serious. The risk factors associated with its development are still unclear. The purpose of our study was to evaluate the incidence of fistula formation or erosion following transvaginal cervical cerclage and the associated clinical and sociodemographic factors. We conducted a systematic search of PubMed, Medline, and Embase databases to retrieve articles related to transvaginal or transabdominal cervical cerclage. Databases were searched up to July 2021. The study protocol was registered (PROSPERO ID 243542). A total of 82 articles were identified describing cervical cerclage and erosion or fistula formation. A total of 9 full-text articles were included. There were seven case reports and series that described 11 patients who experienced late complications following cervical cerclage. Many of the cerclage procedures were done electively (66.7%). The most common type of cerclage was McDonald (80%). While all cases reported fistula formation, the main location was vesicovaginal fistulas (63.6%). One patient (9.1%) had erosion of their cerclage and another (9.1%) had bladder calculi. Of 75 patients who underwent cerclage in two retrospective case reviews, the overall incidence of fistula was 1.3% and abscess was also 1.3%. Although rare, the most common long-term complication of cervical cerclage placement is fistula formation, particularly vesicovaginal fistulas.